A prospective interventional study to compare T-tube placement and primary closure of common bile duct in patients undergoing choledocholithotomy - Imam, M. Nazar; Prasad, Vijay Shankar; Sharfuddin, Sana; Chettri, Babita (International Surgery Journal, 2022)
Background: Primary closure of common bile duct following choledocholithotomy is now being considered as other possibility to the traditional method. This study is designed to analyse the outcome of primary common bile duct repair in terms of mean operation time, duration of hospital stays and post-operative morbidity. The objective of the study was to assess feasibility of safe primary closure in order to achieve early discharge and define case selection for this purpose. Methods: Study was conducted in Sikkim Manipal institute of medical sciences, gangtok on patients operated between January 2017 and April 2018. Primary closure was performed in 16 patients and choledochotomy with T-tube drainage was performed in 16. The primary endpoints were morbidity, the bile drainage quantity, operative time, post-operative stay, time until return to work and postoperative complications and hospital expenses were recorded for each group. Results: Mean total duration of the surgery was 132.44 minutes in primary closure group while it was 146.31 minutes in T-tube group and this difference of around 14 minutes between two groups was statistically significant. Patients were discharged on the 9th day at average in the primary closure group, while in the T-tube they were discharged on the 13th day on average. This difference was statically significant. Conclusions: Primary choledochorraphy is a safe option in selected patients undergoing choledocholithotomy, provided common bile duct patency and clearance can be confirmed intra-operatively.